Effects of Ulva sp. Extracts on the Growth, Biofilm Production, and Virulence of Skin Bacteria Microbiota: Staphylococcus aureus, Staphylococcus epidermidis, and Cutibacterium acnes Strains - Mathilde Fournière; Gilles Bedoux; Djouhar Souak; Nathalie Bourgougnon; Marc G. J. Feuilloley; Thomas Latire (Molecules, 2021)
Ulva sp. is known to be a source of bioactive compounds such as ulvans, but to date, their biological activity on skin commensal and/or opportunistic pathogen bacteria has not been reported. In this study, the effects of poly- and oligosaccharide fractions produced by enzyme-assisted extraction and depolymerization were investigated, for the first time in vitro, on cutaneous bacteria: Staphylococcus aureus, Staphylococcus epidermidis, and Cutibacterium acnes. At 1000 μg/mL, poly- and oligosaccharide fractions did not affect the growth of the bacteria regarding their generation time. Polysaccharide Ulva sp. fractions at 1000 μg/mL did not alter the bacterial biofilm formation, while oligosaccharide fractions modified S. epidermidis and C. acnes biofilm structures. None of the fractions at 1000 μg/mL significantly modified the cytotoxic potential of S. epidermidis and S. aureus towards keratinocytes. However, poly- and oligosaccharide fractions at 1000 μg/mL induced a decrease in the inflammatory potential of both acneic and non-acneic C. acnes strains on keratinocytes of up to 39.8%; the strongest and most significant effect occurred when the bacteria were grown in the presence of polysaccharide fractions. Our research shows that poly- and oligosaccharide Ulva sp. fractions present notable biological activities on cutaneous bacteria, especially towards C. acnes acneic and non-acneic strains, which supports their potential use for dermo-cosmetic applications.